An Analysis of Theory of Planned Behavior (TPB) on Revisit Intention : Mediating Effect of Attitude to Visit - Yudi Haliman; Petrus Sentoso Tan (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study investigates the influence of intention to revisit homestays in Indonesia as a mediator of the interaction between e-service quality, destination image, subjective norms, and intention to revisit. This study uses a cross-sectional approach and quantitative methods. This study collected primary data to be analysed by scanning the barcode provided on the homestay website. To examine the influence of revisit attitude on the relationship between e-service quality, destination image, and subjective norms on revisit intention, 369 foreign and domestic visitors to homestays in Indonesia were recruited as participants. The study found that neither service quality nor destination image significantly influenced attitude. However, subjective standards had a significant influence on attitude. The study revealed that destination image and subjective norms have a favourable and statistically significant influence on intention to visit. In addition, the results of this study indicate that revisit attitude partially mediates the relationship between subjective norms and revisit intention.